Pemikiran Al-Farabi dan Relevansinya dalam Pengembangan Kurikulum Pendidikan Dasar - Nafsi, Filzatun; Salik, Mohamad; Widianto, Suheri (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Primary education that predominantly emphasizes cognitive achievement has led to a gradual degradation of character education. Consequently, the educational system risks producing graduates who are intellectually capable but morally fragile. This study aims to examine and propose a conceptual framework derived from the thoughts of the Muslim philosopher Al-Farabi as a philosophical foundation for revitalizing the primary education curriculum toward the formation of a holistic human being. This research employs a qualitative method with a library research approach, in which data from Al-Farabi’s primary works and relevant secondary literature are analyzed through descriptive-philosophical analysis. The findings reveal that Al-Farabi’s educational thought is holistic in nature, emphasizing the ultimate goal of attaining true happiness (sa‘adah) through the balance between intellectual cultivation (‘aql) and moral excellence (khuluq). His concept of integrating theoretical sciences (logic, metaphysics) and practical sciences (ethics, politics), along with the central role of the teacher as a moral exemplar, holds significant relevance for addressing the persistent dualism between cognition and character in modern education. The study concludes that Al-Farabi’s philosophy can be actualized through a curriculum that harmonizes philosophical, pedagogical, and curricular dimensions, thereby nurturing a generation that is not only intellectually superior but also morally upright and socially conscious.